Anatomic features of Juniperus sabina growing in the Central Kazakhstan - Abdikarimova, P.U.; Atikeeva, S.N. (Karagandy University of the name of acad. E.A. Buketov, 2023)
Anatomical parameters of the needles of the Cossack juniper growing in different geographical regions (the city of Karaganda, Karkaraly, Zhanaarka and Ulytau districts) were studied. During the research work of Juniperus sabina in the populations of Ulytau and Karkaraly districts, the development of hypoderma is not so great, and in the populations of Juniperus sabina of Zhanaarka district, good development of hypoderma, cuticle and epidermis can be observed. This in turn reflects the adaptation of plants to the harsh growing conditions in such regions. Descriptive statistics were arithmetic averages, standard deviations, coefficients of variation, according to the data of each geographic region, each population.
Орталық Қазақстанда өсетін Juniperus sabina анатомиялық ерекшеліктері
Анатомические особенности Juniperus sabina, произрастающей в Центральном Казахстане
Keywords: coefficient of variation; cossack juniper; anatomy; transverse incision; size of the conducting beam; epidermis; cuticle; hypoderm